Influencer, Viral Marketing, FOMO Regarding Purchase of Emina Skincare at Rumah Kosmetik Carissa Lempuyang - Pika, Putu Ayu Titha Paramita; Putri, Rizkana Nazlia; Sari, Desak Made Febri Purnama (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to determine the effect of Influencer Marketing, Viral Marketing, FOMO on the purchase of Emina skincare at Rumah Kosmetik Carissa Lempuyang. The sample in this study was taken using a non-probability sampling method with a purposive sampling technique with a total of 140 respondents. Data collection was carried out by distributing questionnaires with 28 statement items. Data analysis techniques were carried out using Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, Determination Coefficient Test, t-test, and F-test. Based on the results of the study, it was found that influencer marketing had a positive and significant effect on purchasing decisions, viral marketing had a positive and significant effect on purchasing decisions, FOMO had a positive and significant effect on purchasing decisions, and influencer marketing, viral marketing, FOMO had a joint effect on purchasing decisions. The independent variable was able to explain 62.2% of the variation in purchasing decisions. Suggestions that can be given by researchers are for Emina to pay more attention to its skincare promotions so that consumer attention is not focused on its cosmetic products alone, it is hoped that Rumah Kosmetik Carissa Lempuyang will continue to promote Emina skincare in order to increase Emina skincare sales. It is hoped that this research will provide benefits for future researchers and can be used as a reference for other researchers in the future.